Humanity development library 2.2 - Human Info NGO; Payson Center for International Development and Technology Transfer; CD-ROM Creation and Logistics (Antwerp, Belgium : Human Information Projects, 2000)
A cooperative project to provide sustainable development & basic hum an needs information. 800 books & reports, 400 newsletters, 160,000 pag es of ideas, experiences and solutions, including the environmental han dbook.
CD-ROM creation & logistics: Human Info NGO
November 2000.
Every participating organization or author retains the full exclusiv e copyrights on its publications-Unauthorized copying prohibited.
Compartible with Windows 3.1 & higher, Windows 95/98 & NT; min.: 486 -66 MHz-8 Mb 12 Mb HD. To install start "setup.exe" and follow the inst ructions. Open "Humanity Development Library" and "HDL 2.2". Netscape 4 .6 available on CD-ROM
Keywords: Economic development -- Social aspects; International organization; Humanitarianism